The value of a trademark - Sichel, Debora Lacs (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The paper discusses how trademarks are legally regulated, and how their value is established, considering trademarks in the context of products and services, brands, and innovation processes. The author analyses how the aforesaid factors condition consumer’s way of perceiving trademarks, pointing out that what a man needs is not what a consumer buys. The author concludes that the above-mentioned factors have a decisive impact on establishing the value of a trademark. They may not have a direct influence on physical assets of a titleholder, but they impact plans made by the management in order to advertise a product or a service
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 474, s. 65-76
Keywords: brand; trademarks; value; marka; znak handlowy; wartość